MELKI DAN JOHNY CALON GUBERNUR DAN WAKIL GUBERNUR NUSA TENGGARA TIMUR - Djawa, Alex (Jurnal Lazuardi, 2024)
The elections for governor/deputy governor, regent/deputy regent, mayor/deputy mayor will take place on November 27. The candidates who are fighting and competing continue to carry out various approaches and activities to convince the public to vote for them. One way they get closer to the community is by conveying messages and information through billboards. An approach using this tool seems to be more effective in conveying the characters and their thoughts to the public. This approach is also considered cheaper compared to other approaches.